Primary frequency response from hydrogen-based bidirectional vector coupling storage: modelling and demonstration using power-hardware-in-the-loop simulation - Allahham, Adib; Greenwood, David; Patsios, Charalampos; Walker, Sara Louise; Taylor, Phil (Frontiers in Energy Research, 2023)
To meet reduction targets for carbon emissions and improve the flexibility and security of the energy supply, future energy networks will require enhanced energy vector coupling in addition to the generation of energy from renewable sources. Increased renewable generation penetration significantly affects the electrical grid's inertia and consequently the severity and regularity of frequency deviations from nominal values. Bidirectional Hydrogen-based Vector Coupling Storage (VCS) has been explored as a means to provide primary frequency response (PFR) services to the electrical network. This paper demonstrates the use of Power Hardware-In-the-Loop (PHIL) simulation and Digital Twin (DT) technique for such an application. This new suggested structure of VCS is composed of grid-scale electrolysers, fuel cells, and hydrogen storage. Existing works focus on unidirectional VCS, and also use simplifications or neglect the impacts of power converters on the performance of the VCS. In addition, these works do not have any control over the hydrogen storage, therefore there is no guarantee that there will be enough energy available in the storage to meet the PFR service responsibilities. This paper presents the dynamic models of electrolysis, fuel cell stacks, and hydrogen storage as a DT. The key parameters affecting the behaviours of these main components are considered. The power converters' accurate impact on the VCS's performance is considered through PHIL simulations. The level of stored hydrogen is also considered in the VCS controller. The DT representing the VCS is integrated with the PHIL setup representing the deployment environment. The impact of VCS is then analysed as it propagates to the deployment environment. Results of the considered case studies demonstrate that the size of the VCS plays a significant role in bringing the frequency to the statutory allowed range. In addition, more VCS capacity was installed, the nadir frequency improved. Furthermore,the VCS is fast enough to offer PFR. The response times of the VCS were 2.857 s (during under-frequency periods), corresponding to the operation of the fuel cells, and 2.252 s during over-frequency periods, corresponding to electrolyser operation.